AN ELECTRONICALLY TUNABLE OSCILLATOR USING A SINGLE ACTIVE DEVICE AND TWO CAPACITORS - Koksal, M.; Sagbas, M.; Sedef, H. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2008)
A novel resistorless oscillator is presented. The proposed structure enjoys electronic tunability property with minimum number of active and passive components. This oscillator uses a current-mode (CM) active device and has properties of current mode circuits. The validity of the proposed circuit is verified by experimental results.
Keywords: Current differencing buffered amplifier; sinusoidal oscillator; current controlled oscillator; electronic tunability; DIFFERENCING BUFFERED AMPLIFIER; CURRENT CONVEYOR; FILTERS; Computer Science; Engineering